Equally As A Pattern For Resolving Rights Disputes In The Work Environment (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to verify the effectiveness of equally as an independent strategy for resolving conflicts in the work environment. As well as the significance of the differences in the views of the employees of the University of Duhok about the use of equally as a pattern for resolving conflicts according to the demographic variables: (age, college, and gender). The study relied on the quantitative method using the field study tool represented in the questionnaire. To obtain inputs that can be dealt with according to the scientific contexts followed in such studies. The objective limits of the study are labor disputes. It is limited to contentious relationships or conflicts among the employees themselves. Without addressing disputes over interests of a collective nature. The study sample consisted of (250) male and female employees who were randomly selected from the University of Duhok employees. Those who answered the questionnaire that was prepared for the purposes of the research, which included (20) paragraphs, and in front of each paragraph there were five alternatives to the answer: (strongly agree, agree, to my opinion, disagree, strongly disagree).The data were processed statistically using the t-test for one sample and two independent samples and one-way analysis of variance, and the results showed a high level of approval of the use of equally as a pattern of conflict resolution among university employees in general. It was found that there were no significant differences in the views of Duhok University employees regarding the use of equally as a pattern for resolving conflicts according to the variables of age, college and gender.